Spatial Association Between Dog Ownership and Crime Rate in New York City - Ahmad Ilderim Tokey; Shefa Arabia Shioma (Findings)
This paper identifies the spatial relationship between dog ownership and the property crime rate in New York City. This zip-code level study reveals that the dog ownership rate in 2019 positively correlates with the crime rate in past three years (2016-2018). It also finds that areas with high poverty rates, high proportions of Asian and Black people, and larger households (more than two) have lower dog-ownership rates than their counterparts. Areas with denser sidewalks also correlate with high dog-ownership rates. The finding underscores the role of dogs in increasing the feeling of safety in high crime rate areas.